Respiratory and swallowing rehabilitation in a patient with ischaemic stroke and tracheostomy - Micaela Figueroa, Aldana; Patrinos, Alejandro (International Journal of Neurology, 2023)
The study analysed the clinical evolution and rehabilitation process of an adult patient who suffered an ischaemic cerebellar and left temporal stroke, requiring prolonged hospitalisation in the Intensive Care Unit and mechanical ventilation. It was reported that, due to acute neurological compromise, the patient required orotracheal intubation and subsequently tracheostomy, which allowed ventilation to be maintained but led to the onset of multiple complications. During the stay in the ICU, frequent complications in critical patients were recorded, such as ventilator-associated pneumonia, iron deficiency anaemia, urinary tract infections, and clostridial diarrhoea, which negatively affected functional recovery. Neurologically, significant motor sequelae were evident, including right central facial paralysis, right brachial plegia, and right crural paresis, with gait and coordination impairments. A central focus of the analysis was the presence of multifactorial dysphagia, attributed to both neurological damage and disuse of the pharyngolaryngeal structures secondary to prolonged intubation and tracheostomy. Clinical and instrumental evaluation identified a high risk of aspiration, which limited progress toward decannulation. The therapeutic approach was developed in an interdisciplinary manner, integrating respiratory kinesiology and speech therapy, with strategies aimed at ventilatory weaning, stimulation of oropharyngeal sensitivity, motor rehabilitation, and control of sialorrhea through pharmacological and non-pharmacological interventions. Although decannulation was not achieved during the period analysed, a partial improvement in secretion management and respiratory function was observed. The case highlighted the importance of early diagnosis and comprehensive treatment of post-stroke dysphagia to improve functional prognosis and quality of life.